Cultural barriers for doing business in Europe for businessmen from the Middle East - AlQudah, Hamza; Semenenko, Vadim; Chvátalová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
When opening a business in Europe as a Middle Eastern entrepreneur, it's far vital to recognize the various negotiation styles across different countries. Negotiation techniques can range extensively from one country to another. Some cultures emphasize formal and dependent negotiations, while others prioritize building personal connections. Certain regions may focus on consensus-building, while others adopt a more assertive style. Adapting to those numerous negotiation patterns requires understanding the customs and preferences of the target country, adjusting strategies accordingly, and developing cross-cultural negotiation skills. Seeking local knowledge and guidance can also prove valuable in navigating those differences successfully.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses